2014
DOI: 10.1161/atvbaha.114.303950
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Neutrophil Gelatinase-Associated Lipocalinin in the General Population

Abstract: Objective— Neutrophil gelatinase-associated lipocalin (NGAL) is a glycoprotein stored in granules of neutrophil leukocytes participating in inflammatory and atherosclerotic processes and possibly plaque rupture. Despite the putative role of NGAL in atherosclerosis and acute myocardial infarction, human studies of plasma NGAL are still limited. Approach and Results— We prospectively followed 5599 randomly selected men and women from the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 33 publications
(24 reference statements)
5
38
1
2
Order By: Relevance
“…The colocalization of NGAL with matrix metallo protein 9 (MMP-9) in plaques and infarcted hearts suggests a role for NGAL in the MMP-9 mediated remodeling (Hemdahl et al, 2006). In a 10-year follow up study performed in a healthy population, higher baseline NGAL levels were associated with adverse cardiac events and all-cause mortality (Lindberg et al, 2014). The association of higher NGAL levels with cardiovascular risk was previously reported in a population of community dwelling elderly (Daniels et al, 2012).…”
Section: Function Of Ngal In Cardiovascular Diseasementioning
confidence: 77%
See 1 more Smart Citation
“…The colocalization of NGAL with matrix metallo protein 9 (MMP-9) in plaques and infarcted hearts suggests a role for NGAL in the MMP-9 mediated remodeling (Hemdahl et al, 2006). In a 10-year follow up study performed in a healthy population, higher baseline NGAL levels were associated with adverse cardiac events and all-cause mortality (Lindberg et al, 2014). The association of higher NGAL levels with cardiovascular risk was previously reported in a population of community dwelling elderly (Daniels et al, 2012).…”
Section: Function Of Ngal In Cardiovascular Diseasementioning
confidence: 77%
“…In a study of NGAL in a healthy population, NGAL was associated with other markers of inflammation, including Creactive protein and neutrophil count (Lindberg et al, 2014). NGAL levels are upregulated in different autoimmune disorders (Shashidharamurthy et al, 2013;Rubinstein et al, 2008).…”
Section: Ngal and Inflammationmentioning
confidence: 99%
“…A human prospectively investigation found that this glycoprotein was positively associated with cardiovascular events including atherosclerotic disease. 75 These two recent human studies provide clinical evidence that neutrophils may play an important role in the development of atherosclerosis. 76 …”
Section: Inflammation In Atherosclerosismentioning
confidence: 97%
“…By contrast, eGFR was mainly associated with plasma NGAL when eGFR was reduced [15]. Accordingly, we speculate that in healthy humans, plasma NGAL mainly reflects inflammation, whereas the kidney only contributes to plasma NGAL in the setting of chronic kidney disease or AKI.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, when eGFR is in the normal range (>60 ml/min) eGFR contributes little to plasma NGAL [15]. …”
Section: Discussionmentioning
confidence: 99%